Bentuk Pernikahan Arab Quraisy Pada Masa Jahiliyah dan Perubahan Bentuk Pernikahan Di Masa Awal Islam - Pamungkas, Jati (Prodi Studi Agama-agama Fakultas Ushuluddin dan Dakwah IAIN Kediri, 2022)
Marriage is an important part of culture in a tribe or ethnicity. With marriage, it is hoped that a new generation will be born who will continue the traditions and culture of the previous generation. The existence of this new generation can prevent a tribe, ethnicity and even a nation from extinction. So marriage has a very decisive influence. In Arab culture, especially the Quraysh tribe in Mecca, there are some interesting things about the types of marriage, especially marriage before Islam. This study uses a literature review method because with this method it will be easy to find historical facts about the marriage of the Quraysh tribe in the jahiliyah period. This study describes the types of marriage practiced by the Quraysh tribe in Mecca during the jahiliyah period and change of the types of mariage in early Islam.